Surgical treatment of lingual goiter. - Pittamiglio, Horacio; Blasiak, José; Jorge, Ana M (Cirugía del Uruguay, 1985)
An extense bibliographic revision is done with the presentation of a case of lingual goiter. Diagnostic and therapeutic norms are said. The good evolution of th• yroid implants is documented.